Prognostic value of α2δ1 in hypopharyngeal carcinoma: A retrospective study - Liu Qiang (De Gruyter, 2021)
Voltage-dependent calcium channel subunit alpha-2/delta-1 (α2δ1) has been identified as a marker of cancer stem cells in multiple malignant tumor types. However, α2δ1’s role in the prognosis of hypopharyngeal squamous cell carcinoma (HSCC) was not reported. In our study, ten pairs of HSCC and peritumoral normal tissues were used for immunohistochemistry assessment. And α2δ1 expression levels of 34 more HSCC samples were also evaluated, represented by the integral optic density using Image-Pro Plus. Clinicopathological associations and prognostic value of α2δ1 were analyzed. As a result, α2δ1 expression was frequently increased in HSCC tissues. Although the correlation between patients’ clinicopathological characteristics and their α2δ1 expression levels was not significant, α2δ1 expression was significantly correlated with unfavorable overall survival (OS) (P = 0.018) and progression-free survival (PFS) (P = 0.023). Univariate and multivariate cox regression analyses suggested α2δ1’s prognostic role for both OS and PFS (P = 0.013 and 0.011, respectively). This study specifically demonstrated that α2δ1 regularly increased in HSCC compared with peritumoral tissues, and α2δ1 could act as a promising prognostic marker in HSCC patients.